Dynamic and Nonlinear Analysis of Hybrid Epoxy Composites: Impact of Thickness, andTransient Behavior - Qamili, Aurela; Dindi, Ana; Hoxha, Adhurim; Sheikhaleslami, Z. (Karshi Multidisciplinary International Scientific Journal, 2024)
This study investigates the thermal and electrical performance of hybrid epoxy composites with varying thicknesses, filler fractions, and nonlinear material behaviors. The effect of composite thickness on conductivity was examined by extensive MATLAB simulations, which showed that while electrical conductivity falls with increasing resistance, thermal conductivity increases with thickness. Higher filler fractions are perfect for dynamic applications since they drastically shorten the time needed to reach steady-state conditions, as shown by transient simulations. By demonstrating how temperature- and voltage-dependent conductivities yield more accurate predictions than linear models, the study further emphasizes the significance of nonlinear modeling. These results highlight how important filler content, composite geometry, and nonlinear effects are when it comes to developing hybrid composites for high-performance uses. Experimental validation, investigation of sophisticated filler configurations, and examination of other nonlinear behaviors are among the suggestions for further research. This research advances the creation of hybrid epoxy composites with improved electrical and thermal characteristics for application in the automotive, aerospace, and electronics sectors.